PENDAMPINGAN IMPLEMENTASI HAZARD ANALYSIS CRITICAL CONTROL POINT (HACCP) DAN PENGENDALIAN MUTU BORAKS "CV SOLO MARSUDI LUHUR” MOJOLABAN, SUKOHARJO. - Safira (Airlangga Journal of Innovation Management, 2024)
The quality and food safety management system currently implemented is HACCP (Hazard Analysis Critical Control Point). Supporting factors that are prerequisites for the effectiveness of implementing HACCP as a quality control system is the fulfillment of basic feasibility requirements. This research uses a qualitative approach. The method used is descriptive verification to obtain an accurate and actual picture of the facts and nature of the relationships between phenomena discovered by CCP in the process flow. Problems that occur in the development of home industries such as the non-borax onion shell processing business include low quality, quality, quality control, and food safety. So, to achieve good quality puli crackers and according to the required criteria, namely SNI No.01-4307-1996, supervision and control need to be carried out at every stage of the process, starting from receiving raw materials until the product is ready to be marketed. On the other hand, a quality control concept system is needed to minimize errors in the production process and the risk of food safety hazards, one of which is by implementing the Hazard Analysis Critical Control Point (HACCP) concept. From the results, this research can be concluded that the shell processing unit at the research location at CV Marsudi Luhur has not implemented a quality control system and HACCP properly. Research result It is hoped that this can be used as a basis for further research on quality and safety assurance of food and environmental quality for making non-borax onion shells around the Sukoharjo district.